Kidney transplantation beyond immunosuppression: shifting the focus from graft survival to patient health - Moroni, Gabriella; Reggiani, Francesco; Ponticelli, Claudio (Frontiers in Immunology, 2026)
Kidney transplantation has traditionally focused on maximizing graft survival, with immunosuppressive therapy as the cornerstone of care. However, long-term patient health requires a broader perspective that addresses the prevention and management of post-transplant complications. This review explores strategies extending beyond immunosuppression, emphasizing the joint responsibility of patients and clinicians in achieving optimal outcomes. Patients play a pivotal role through adherence to lifestyle measures, including regular physical activity, balanced nutrition, meticulous hygiene, infection prevention, and sun protection to reduce skin cancer risk, as well as strict compliance with prescribed therapies. These self-care practices can significantly lower the incidence of infections, cardiovascular disease, and malignancies. Clinicians, in turn, must adopt a proactive, comprehensive approach to surveillance and early intervention. This includes timely recognition and management of cardiovascular complications, vigilant cancer screening, and infection control tailored to individual risk profiles. By integrating patient education, lifestyle optimization, and vigilant clinical oversight, kidney transplant care can shift from a narrow focus on graft survival toward a holistic model prioritizing overall patient well-being and longevity. Such an approach recognizes that the success of transplantation is measured not only in years of graft function, but in the quality and health of the patient’s life.